2023
DOI: 10.1038/s41380-023-02206-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to environmental air pollution and psychosocial stress jointly contribute to the epigenetic regulation of the serotonin transporter gene in newborns

Abstract: Antenatal exposures to maternal stress and to particulate matter with an aerodynamic diameter of less than 2.5 μm (PM 2.5 ) have been independently associated with developmental outcomes in early infancy and beyond. Knowledge about their joint impact, as well as possible biological mechanisms of their effects, is still limited. Both PM 2.5 and maternal stress exposure during pregnancy might result in altered patterns of DNA methylation in speci c stress-related genes, such as the serotonin transporter gene (SL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Studies have shown that exposure to climate-related disasters can lead to increased rates of post-traumatic stress disorder, anxiety, and depression in children (Sharpe and Davison, 2021 ; Rothschild and Haase, 2023 ). Furthermore, not only the direct exposure to polluted environments (Shezi and Wright, 2018 ; Nazzari et al, 2023 ; Pili et al, 2024 ), but also the chronic stress associated with the uncertainty and fear surrounding climate change can have long-lasting effects on children's emotional development and resilience (Léger-Goodes et al, 2022 ). While the consequences of this environmental crisis are wide-ranging, one area often overlooked is its profound impact on the mental health of our children.…”
Section: A Looming Storm: Climate Change and Child Developmentmentioning
confidence: 99%
“…Studies have shown that exposure to climate-related disasters can lead to increased rates of post-traumatic stress disorder, anxiety, and depression in children (Sharpe and Davison, 2021 ; Rothschild and Haase, 2023 ). Furthermore, not only the direct exposure to polluted environments (Shezi and Wright, 2018 ; Nazzari et al, 2023 ; Pili et al, 2024 ), but also the chronic stress associated with the uncertainty and fear surrounding climate change can have long-lasting effects on children's emotional development and resilience (Léger-Goodes et al, 2022 ). While the consequences of this environmental crisis are wide-ranging, one area often overlooked is its profound impact on the mental health of our children.…”
Section: A Looming Storm: Climate Change and Child Developmentmentioning
confidence: 99%